The Influence of Online Queue Implementation, Service Quality, and Digital Literacy on Patient Satisfaction at Puskesmas M Surabaya - Ranti Ana Ningsih; Kosasih; Taufan Nugroho; Vip Paramarta; Farida Yuliaty (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of online queue implementation, service quality, and digital literacy on patient satisfaction at Puskesmas M Surabaya. A quantitative approach with descriptive and verificative methods was employed. Data were collected via questionnaires distributed to 97 respondents, determined using the Slovin formula from a population of 3,059 outpatients. Multiple linear regression was conducted using SPSS. Results indicate that online queue implementation (X1) has a positive but non-significant effect on patient satisfaction (β = 0.148; Sig. = 0.059), while service quality (X2) (β = 0.393; Sig. = 0.000) and digital literacy (X3) (β = 0.345; Sig. = 0.000) have a positive and significant effect, both partially and simultaneously (F = 11.918; Sig. = 0.000). The coefficient of determination R² = 0.670 indicates that 67% of patient satisfaction variance is explained by the three variables. These findings affirm that humanistic service interactions and patient digital literacy are critical complements to digital transformation in primary healthcare settings.